mTORC2 controls actin polymerization required for consolidation of long-term memory. - Huang, W.; Zhu, P.J.; Zhang, S.; Zhou, H.; Stoica, L.; Galiano, M.; Krnjevi?, K.; Roman, G.; Costa-Mattioli, M. (Nature Neuroscience, 2013)
A major goal of biomedical research is the identification of molecular and cellular mechanisms that underlie memory storage. Here we report a previously unknown signaling pathway that is necessary for the conversion from short- to long-term memory. The mammalian target of rapamycin (mTOR) complex 2 (mTORC2), which contains the regulatory protein Rictor (rapamycin-insensitive companion of mTOR), was discovered only recently and little is known about its function. We found that conditional deletion of Rictor in the postnatal murine forebrain greatly reduced mTORC2 activity and selectively impaired both long-term memory (LTM) and the late phase of hippocampal long-term potentiation (L-LTP). We also found a comparable impairment of LTM in dTORC2-deficient flies, highlighting the evolutionary conservation of this pathway. Actin polymerization was reduced in the hippocampus of mTORC2-deficient mice and its restoration rescued both L-LTP and LTM. Moreover, a compound that promoted mTORC2 activity converted early LTP into late LTP and enhanced LTM. Thus, mTORC2 could be a therapeutic target for the treatment of cognitive dysfunction.